Acta Historiae Neerlandicae IX - Baetens, R. author. aut Link
VIII, 245 p. 2 illus.
Keywords: In the Survey of Recent Historical Works, which according to custom concludes this IXth volume of the Acta, is a notice of the recent 'Report of the Dutch research, with suggestions for future development'. Such a report could easily be classified as an attempt to bring pressure to bear on financial resources for support of a somewhat neglected branch of scientific effort, indeed as a symptom of the current disease of notatitis. A recent special issue 'Regeren door notas', of the periodical Beleid and Maatschappij, March-April 1976, discusses this severe Dutch epidemic of official note-writing, for any purpose, on any matter, at any time, by any sort of official committee to any sort of official body. But even if such were the only reason for the production of this Report, which indeed it is not, the Report will stand on its own feet, as significant and of consequence. In general, however, this Report makes sad reading. It would seem that Dutch historical research and historiography lags far behind comparable foreign developments. There are said to be immense gaps in knowledge of and insight into virtually all fields of the Dutch past and moreover a total lack of modem sophistication. Inevitably, currently fashionable techniques such as programming, co-ordination, and teamwork are suggested as desirable, and a preference is expressed for the currently highly regarded socio-historical approach.